Harmonisasi Hukum Negara dan Norma Adat: Analisis Sosiologis atas Penyelesaian Sengketa Tanah Adat di Indonesia - Aini Rahma Ramadhani, Qurrota; Kamilah, Anita; Mulyana, Aji; Yulianah, Yuyun (Journal of Contemporary Law Studies, 2025)
This study aims to analyze the role of law in resolving customary land disputes in Indonesia through a sociological perspective, focusing on the interaction between formal legal frameworks and social norms within indigenous communities. Employing a qualitative-descriptive approach and case study method, the research examines selected customary land conflicts and relevant literature on agrarian law and indigenous rights. The findings reveal that such disputes are often triggered by unclear land status, limited public understanding of customary (ulayat) rights, and a disconnect between state law and customary law. Law plays a crucial role as a conflict resolution tool, but its effectiveness largely depends on successful mediation between formal regulations and local values. This study highlights the need to enhance legal awareness among indigenous communities and the importance of collaboration between the government and local stakeholders in creating inclusive and equitable land registration systems. In conclusion, a solid understanding of agrarian law and respect for customary rights are essential to prevent conflicts and ensure social justice. The study recommends strengthening legal documentation of land ownership and improving empirical data on customary land disputes to inform more effective policy interventions.